Treatment of infrabony defects with platelet-rich fibrin along with bone graft: Case report - Surekha Y Bhedasgaonkar; Janak Kapadia; Neha A Patil (Wolters Kluwer Medknow Publications, 2015)
Although periodontitis is an infectious disease of periodontal tissues, changes that occur in the bone are crucial, because destruction of bone is responsible for tooth loss. Although horizontal bone loss is most common, vertical bone loss is more amenable to regenerative periodontal therapy. Recently, importance has been given to use of platelet-rich fibrin (PRF) for predictably obtaining periodontal regeneration. PRF is a concentrated suspension of growth factors found in platelets. These growth factors moderate the wound healing and promote tissue regeneration. This article includes case reports of two patients who showed infrabony defects that were treated with combining PRF with allograft. This case report tried to compare the clinical and radiographical outcome obtained by combination of PRF and allograft.